1988
DOI: 10.1007/bf00215463
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-dependent changes in TSH-like immunoreactivity of cells in the hypophysial pars tuberalis of the Djungarian hamster, Phodopus sungorus

Abstract: Certain secretory cells in the hypophysial pars tuberalis of the Djungarian hamster display marked circannual structural alterations. The present investigation deals with the immunohistochemical properties of this cell group. A distinct TSH-like immunoreactivity was found in secretory cells of this type in the pars tuberalis of animals exposed to long photoperiods, whereas under short photoperiods the TSH-like immunoreactivity was nearly absent. In the pars distalis, the number and distribution of TSH-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 17 publications
3
63
0
Order By: Relevance
“…It has been reported that the expression of CGA and TSHb in the mammalian pars tuberalis are photoperiodically regulated (Wittkowski et al 1988, Bockmann et al 1996, 1997. Furthermore, the expression of TSH has been detected in the CSF and CNS (Schaub et al 1977, Hojvat et al 1982 of mammals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the expression of CGA and TSHb in the mammalian pars tuberalis are photoperiodically regulated (Wittkowski et al 1988, Bockmann et al 1996, 1997. Furthermore, the expression of TSH has been detected in the CSF and CNS (Schaub et al 1977, Hojvat et al 1982 of mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although they express the same hormones, TSH-immunoreactive cells in the PT and in the PD are not physiologically regulated in the same way. Wittkowski et al (1988) have shown that the TSH content of PT-specific cells is strongly reduced in Djungarian hamsters subjected to short days compared to long days. Because this effect is prevented by pinealectomy and can be mimicked by injections of melatonin, it appears that melatonin is a major regulator of TSH expression in the PT (Böckers et al 1995; Bockmann et al 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Poult. Sci., 10 (1): 52-63, 2016 stimulate and release of thyroid hormones (Wittkowski et al, 1988). Thyroid hormones especially T 3 have a multiple effects on vertebrate metabolism and development.…”
mentioning
confidence: 99%